Design And Simulation Of Lte Radio System For Broadband Wireless Access In Central Phnom Penh - Siren Seven; Rina Pudji Astuti; Budi Prasetya (eProceedings of Engineering, 2015)
Abstract—The huge number of users and new applications need higher  access  speeds  and  lower  latency  of  wireless communication. As a result, operators need more capacity and higher efficiency to serve their costumer. LTE is designed to have wider channels up to 20MHz, with low latency and packet optimized radio access technology. The peak data rate envisaged for LTE is 100 Mbps in downlink and 50 Mbps in the uplink. In order to support the simultaneous use of legacy and new systems, the operator need to provide a better radio system, especially in central  Phnom  Penh.  The  aim  of  this  study  is  to  designs, simulates,  analyzes  and  expose  the  state  of  the  art  of  map planning LTE radio system. Special emphasis is laid on radio link budget  along  with  detailed  coverage  area  and  capacity.  The results cover the interference limited coverage calculation, the traffic capacity calculation and radio frequency assignment. The implementation is achieved on the software platform for the LTE Radio  Planning  and  also  can  see  the  simulation  antenna  in Google Earth. The study will present a detailed LTE radio dimensioning procedure such as coverage area and capacity in Phnom Penh city. The simulation and analysis of the coverage by signal level and overlapping zone also a part of this work. Keywords— Long Term Evolution; MIMO; Coverage area; Capacity; Cost 231-Hata.